2020
DOI: 10.1038/s41746-020-00352-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a deep-learning system for fracture detection in musculoskeletal radiographs

Abstract: Missed fractures are the most common diagnostic error in emergency departments and can lead to treatment delays and long-term disability. Here we show through a multi-site study that a deep-learning system can accurately identify fractures throughout the adult musculoskeletal system. This approach may have the potential to reduce future diagnostic errors in radiograph interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…including the upper and lower extremities and spine (13), but the clinicians who read the radiographs with AI and without AI assistance were emergency medicine physicians and physician assistants only, with senior orthopedic surgeons providing the ground truth; no radiologist was involved in the radiographic interpretation. Another recent study analyzed fractures in 16 anatomic locations; however, readers of the radiographs were radiologists and orthopedic surgeons only (14).…”
Section: Ground Truth Definitionmentioning
confidence: 99%
“…including the upper and lower extremities and spine (13), but the clinicians who read the radiographs with AI and without AI assistance were emergency medicine physicians and physician assistants only, with senior orthopedic surgeons providing the ground truth; no radiologist was involved in the radiographic interpretation. Another recent study analyzed fractures in 16 anatomic locations; however, readers of the radiographs were radiologists and orthopedic surgeons only (14).…”
Section: Ground Truth Definitionmentioning
confidence: 99%
“…In particular, virtual fracture clinic review [25] and out-of-hours teleradiology services [26] have been widely adopted across the UK and Europe. Alongside these existing methods, the development of novel technologies (such as artificial intelligence algorithms [27]) to supplement interpretation is evidence of a broadly accepted clinical need to improve this reporting.…”
Section: Key Findingsmentioning
confidence: 99%
“…Recently, deep learning algorithms, especially convolutional neural network (CNN) architectures, have been widely recognized as an outperforming and reliable approach to identify clinically useful features directly from the medical images. ( 18 ) Previous studies that used CNNs showed promising results in radiology, ( 19 ) pathology, ( 20 ) ophthalmology, ( 21 ) surgery, ( 22 ) and laboratory medicine. ( 23 ) With the continuous improvement of the CNN architecture and the rapid increase in hardware computing power, CNNs have achieved human‐level recognition performance.…”
Section: Introductionmentioning
confidence: 99%